Breast Cancer Screening with Mammography at Kasugai City Medical Care Center - Kobayashi, Naomi; Miura, Kaoru; Oohashi, Isao; Sobue, Isao; Inagaki, Asako; Iwase, Katsumi; Ogawa, Hirotoshi; Jimbo, Shin (Journal of Japan Association of Breast Cancer Screening, 1998)
Recently, breast cancer screening with mammography has been recommended for detection of early cancer. We have carried out mammography screening for women aged over 30 years at Kasugai City Medical Care Center over the last 3 years. Every examinee underwent physical examination by a surgeon and mammography, and those who had abnormal findings and were unsuitable for mammography underwent ultrasonography. Sixteen breast cancer patients with a detection rate of 0.51% were found by the screening. Eleven tumors were palpable, 14 were detected by mammography, and 15 were detected by ultrasonography. Eleven of the 16 cancers were found at an early stage (stage 0 or I) and 5 were treated by partial mastectomy. Fibroadenoma was found in 16 of 121 women who received further examinations. Thirteen of the fibroadenomas were detected by mammography and 7 of them were not palpable. In 8 cases, malignancy could not be completely ruled out. Forty-one patients considered to have benign lesions at the screening were further examined during the first half of the study period, and only one case of cancer was found. Therefore, we omitted the examinees with obviously benign lesions from further examination in the second half of this period. Consequently, the number of examinees who required further examination was markedly decreased without any decrease in the cancer detection rate. In conclusion, breast cancer screening with physical examination and mammography is excellent for detecting early cancer. Furthermore, the ultrasonography is useful for further observation of lesions found by screening, and in patients who are unsuitable for mammography. The use of mammography or ultrasonography for screening increases the number of patients who require further examination, increases the psychological burden on examinees and raises medical expenditure. But the keeping better quality of the screening can improve these drawbacks.